Evaluasi Kualitas Layanan Sistem Informasi Akademik UIN Maulana Malik Ibrahim Malang Menggunakan Kombinasi E-S-Qual dan E-RecS-Qual - Ghufrani Kusuma Purnamasari; Yusi Tyroni Mursityo; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sistem Informasi Akademik (SIAKAD) UIN Maulana Malik Ibrahim Malang is a website-based information system developed by the Bagian Administrasi dan Akademik of UIN Maulana Malik Ibrahim Malang. However, the services provided are still not maximal, proved by the fact that there are still many students who experience problems while using the Sistem Informasi Akademik. The objective of this study to determine the service quality of Sistem Informasi Akademik UIN Maulana Malik Ibrahim Malang in variable system availability, efficiency, privacy, fulfillment, responsiveness, contact, compensation and perceived value. And give recommendations to UIN Maulana Malik Ibrahim Malang to improve the service quality of SIAKAD. The study population consisted of students of UIN Maulana Malik Ibrahim Malang grade 2013-2017, with 120 respondents as sample.Furthermore the service quality of Sistem Informasi Akademik was analyzed using descriptive statistical analysis to determine the level of the average category of each variable, so that the results of the average category were obtained. At the end of the study it was determined that several variables obtained a fairly good average category of service quality SIAKAD UIN Maulana Malik Ibrahim Malang, such as system availability, efficiency, fulfillment, responsiveness and privacy variable, while compensation, contact and perceived value variable obtained a not good average category.